PENGGUNAAN ICT PADA LKS BERORIENTASI STS TERHADAP HASIL BELAJAR SISWA KELAS VII SMPN 1 PADANG - Nikmatul Husna (PILLAR OF PHYSICS EDUCATION, 2013)
Objective of this research is to determine  the effect of using ICT in worksheet based STS to learning outcomes of 7th grade students in SMPN 1 Padang. Type of this research is quasi-experiment with Randomized Control Group Only Design. All of 7th grade students in SMPN 1 Padang in academic year 2012/2103 as population of this research. Data of this research was data of learning outcomes.The data was analyzed by the mean equality test. Based on analyzis of data, we can conclude that there was using ICT in worksheet based STS give significance effect to learning outcome of 7th grade students in SMPN 1 Padang for cognitive domains at significance level 5%, but there was no significance effect for affective and psychomotor domains at significance level 5%. Keywords – ICT, Worksheet, STS, Learning Outcomes